New Developments in the PuffinPlot Paleomagnetic Data Analysis Program. (5th November 2019) - Lurcock, P. C.; Florindo, F.
Abstract: PuffinPlot is a program for paleomagnetic data analysis and plotting, first released in 2012 and under continuous development since then. It is free, cross‐platform software and provides both a graphical desktop interface for interactive use and an application‐programmer interface for scripting. We present a major new release of the program, describe significant new features added since the first release, and demonstrate their application to real‐world data. New features include automatic magnetic declination realignment, relative paleointensity calculation, virtual geomagnetic pole determination, calculation of inclination‐only statistics, support for reproducible research via the export of self‐contained data bundles, and support for reading a number of popular paleomagnetic file formats. We also discuss the application of unit tests in ensuring PuffinPlot's long‐term reliability and outline directions for future development of the software. Plain Language Summary: By analyzing the remanent magnetization of ancient rocks and sediments, we can work out the strength and direction of the Earth's magnetic field when they were formed. We do this with laboratory measurements of the magnetic properties of rock samples or sediment cores, combined with treatments to remove any unwanted magnetic signals from them. PuffinPlot is a program which analyses these laboratory measurements to estimate the original magnetic field. In this paper we present a new release of PuffinPlot and describe and demonstrate some of its new features. These include a way to calculate magnetic field directions even when a sediment core has been rotated or when it has no azimuthal orientation, combining multiple measurements to estimate the strength of the original magnetic field, and generating a self‐contained software and data package to let other researchers verify and redo the analysis automatically. We also discuss automated tests which make the software more reliable and features that we plan to include in future releases. Key Points: PuffinPlot is a popular application for paleomagnetic data analysis We document a number of significant features added since the initial release in 2012 Features include declination realignment, VGP and RPI calculation, and data bundle export